2011
DOI: 10.1167/iovs.09-5056
|View full text |Cite
|
Sign up to set email alerts
|

Wet versus Dry Age-Related Macular Degeneration in Patients with Central Field Loss: Different Effects on Maximum Reading Speed

Abstract: The four effects improve the ability to predict MRS reliably for AMD patients. The wet/dry difference is a major finding that may result from the different time courses of the two types of disease, thus involving different types of visuomotor and attentional adaptation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 45 publications
(57 reference statements)
2
47
0
Order By: Relevance
“…12,14,17,18,26 Another study 30 using MP1 microperimetry in patients with wet or dry AMD found that PRL eccentricity was a predictor of RS. The authors argued that the PRL used by patients during a fixation task is also preferentially used during a reading task or is used at least in some critical periods of the reading process.…”
Section: Discussionmentioning
confidence: 99%
“…12,14,17,18,26 Another study 30 using MP1 microperimetry in patients with wet or dry AMD found that PRL eccentricity was a predictor of RS. The authors argued that the PRL used by patients during a fixation task is also preferentially used during a reading task or is used at least in some critical periods of the reading process.…”
Section: Discussionmentioning
confidence: 99%
“…15 Therefore, retinal sensitivity assessed by fundus-related microperimetry may provide more reliable insight into macular function deficiencies than by distance VA or reading performance. Accurate measurement of functional deficiency and determination of the responsible morphological correlate enable a better understanding of AMD by detecting the underlying cause of vision loss, which allows a precise determination of the functional stage and may improve the chance of treatment success.…”
mentioning
confidence: 99%
“…The prevention of oxidative stress at early stages of the disease is therefore considered a potential approach to limiting the severity of AMD. Choroidal neovascularization is responsible for the loss of vision in neovascular AMD [20]. In this process, choroidal capillaries penetrate Bruch's membrane and the RPE.…”
Section: Discussionmentioning
confidence: 99%